PERUBAHAN SOSIAL BUDAYA SUKU SAKAI KAMPUNG MINAS BARAT KECAMATAN MINAS KABUPATEN SIAK - Dewi Ningsih; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
There are so many changes happened in Sakai Tribe community in Kampung Minas Barat Kabupaten Siak guch as : religion changes, economic changes and education changes. They are very advance and it can be seen from the way of thinking, attitude and behavior and their habitual activities. Now they are able to accept new cultures that come in their society. Tihis research is almed to know what changes are happening to them and what factors caused that. This research used qualitative sample using snowball sampling and there are three (3) important respondents in sakai tribe society. Observation and interview were used as colleting data method to know about the real condition of socio culture changes of sakai tribe in kampung minas barat. It was found that sakai tribe have some internal factors which came from their community and eksternal factors which came from outside of their community like technology tools etc.Key Words : Socio-Culture, Changes, Sakai Tribe